Mammary adenectomy followed by immediate reconstruction for treatment of patients with early-infiltrating breast carcinoma: a cohort study - Barros, Alfredo Carlos Simões Dornellas de (2019)
BACKGROUND: Use of mammary adenectomy for breast carcinoma treatment remains controversial. OBJECTIVE: This study aimed to verify the oncological safety of mammary adenectomy and immediate breast reconstruction for treating selected patients with infiltrating breast carcinoma and to evaluate pa-tients’ satisfaction with the reconstructed breasts. DESIGN AND SETTING: Cohort study conducted among patients treated at Hospital Sírio-Libanês, São Paulo, Brazil. METHODS: This study was based on 152 selected patients (161 operated breasts) with infiltrating breast carcinoma who underwent mammary adenectomy and immediate breast reconstruction. In all patients, the diameter of the largest focus of the tumor was less than 3.0 cm, the imaging tumor-nipple distance was greater than 2.0 cm and the pathological assessment showed clear margins. The cumulative incidence of local recurrence (LR), recurrence-free survival (RFS) and overall survival (OS) curves were estimated using the Kaplan-Meier method. After at least one year of follow-up, 64 patients were asked about their satisfac-tion with the reconstructed breast(s). RESULTS: At a mean follow-up time of 43.5 months, seven cases of LR (4.4%), four distant metastases (2.6%) and five deaths (3.3%) were recorded. The five-year actuarial LR-free survival, RFS and OS were 97.6%, 98.3% and 98.3%, respectively. No cases of nipple-areolar complex recurrence were reported. Forty-one patients (64%) indicated a high level of satisfaction with the reconstructed breasts. CONCLUSIONS: Mammary adenectomy is a safe and efficacious procedure for selected patients with ear-ly-infiltrating breast carcinoma and results in a high rate of patient satisfaction with the reconstructed breasts.